Psychometric evaluation of smartphone addiction scale – short version (SAS-SV) among young adults of India - George Felix; Manoj K. Sharma; Nitin Anand; Binukumar Bhaskarapillai; Kalpana Srivastava (Industrial Psychiatry Journal)
Background: Although smartphones have considerable utility, they also have addiction potential. The early detection of problematic smartphone use (PSU) can have significant implications for managing its psychosocial consequences. Smartphone Addiction Scale – Short Version (SAS-SV), initially developed for South Korean adolescents, has emerged as a reliable measure for adults across countries. However, SAS-SV continues to be used unvalidated in India. Aim: To evaluate the psychometric properties of SAS-SV for the Indian adult population. Materials and Methods: Content validation of SAS-SV was done by 10 experts, followed by data collection for validation using a cross-sectional design from 434 participants (Mage = 25.4; SDage = 2.6; 58.8% females). The datasheet consisted of a sociodemographic questionnaire and SAS-SV. Statistical analyses comprised confirmatory factor analysis (CFA), exploratory factor analysis (EFA), reliability analyses, percentiles, and evaluation of sociodemographic variables. Results: SAS-SV’s content validity index was 0.93, and item wordings were adjusted after experts’ feedback. CFA did not show good fit indices; hence, EFA was used, which explained 44% of the variance from a unifactorial model. Cronbach’s alpha was 0.85, McDonald’s Omega was 0.86, and test-retest reliability was 0.81. There were no significant PSU differences in gender, marital status, and occupational status. Higher PSU was associated with lower age, lower education, nuclear family, and more hours of smartphone usage. Conclusion: The current study established the psychometric properties of SAS-SV for the Indian adult population. SAS-SV can be used for assessment and treatment monitoring of PSU.